An innovative model for analysing qualitative data. (14th October 2004) - Sheehan, Michael J.
This paper describes how Denzin's model of interpretive interactionism was used and extended during the analytical phase of a research study. In working through the analytical phase of the research, it was discovered that the chosen methodology of interpretive interactionism did not always provide a clear guideline as to how to follow a logical and coherent process to achieve analytical intentions. Thus, there was seen to be a need to extend and deepen Denzin's model, and the extended, innovative model is presented here. The paper also locates the research study in the context of an organisational change programme focusing on the learning and implementing of group process facilitation skills.